Cation deficiency design: A simple and efficient strategy for promoting oxygen evolution reaction activity of perovskite electrocatalyst. (1st January 2018) - Liu, Hao; Ding, Xifeng; Wang, Lixi; Ding, Dong; Zhang, Shihua; Yuan, Guoliang
Abstract: Developing cost-effective and efficient electrocatalysts for oxygen evolution (OER) is one of the prime important issues to emerging renewable energy technologies. Here, we used a simple and efficient method to enhance OER electrocatalytic activity in the alkaline solution by introducing A-site cation deficiency in SrNb0.1 Co0.7 Fe0.2 O3- δ perovskite, namely Sr1- x Nb0.1 Co0.7 Fe0.2 O3- δ ( x  = 0.02, 0.05 and 0.1, denoted as S0.98NCF, S0.95NCF and S0.90NCF, respectively). A-site cation deficiency results in a shrinkage of crystal structure and a change of element oxidation state according to X-ray diffraction (XRD) and X-ray Photoelectron Spectroscopy (XPS) analysis. The electrochemical OER activity is also greatly improved by a small Sr cation deficiency. Linear voltammetry scanning test, Tafel plots and mass activity analysis demonstrated that Sr0.95 Nb0.1 Co0.7 Fe0.2 O3- δ (S0.95NCF) has the highest OER activity among Sr1- x Nb0.1 Co0.7 Fe0.2 O3- δ perovskite electrocatalysts. This enhancement is attributed to the increased surface oxygen vacancies and enlarged electrochemical surface area (ECSA). This work highlights the importance of introducing A-site cation deficiency in perovskites as a simple and efficient strategy for the promotion of OER activity.